Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/molecules27041384
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polyanionic Cellulose Carbamates by Homogeneous Aminolysis in an Ionic Liquid/DMF Medium

Abstract: Polyanionic cellulose carbamates were synthesized by rapid and efficient homogeneous aminolysis of cellulose carbonate half-esters in an ionic liquid/DMF medium. Cellulose bis-2,3-O-(3,5-dimethylphenyl carbamate), as a model compound, reacted with different chloroformates to cellulose carbonates. These intermediates were subjected to aminolysis, for which both the reactivity of different chloroformates towards C6-OH and the reactivity/suitability of the respective carbonate half-ester in the aminolysis were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The higher reactivity and selectivity of phenyl chloroformate towards C6-OH versus C2-OH and C3-OH have already been reported (Elschner et al 2014;Ganske and Heinze 2018). In a previous study, we have optimized the protocol towards quantitative oxycarbonylation of C6-OH (Bui et al 2022b) and also reported on the optimization and successful aminolysis reaction between the polysaccharidic carbonates (Bui et al 2022a). The obtained phenyl carbonate served as a reactive intermediate for subsequent aminolysis with propargylamine yielding a propynyl carbamate moiety as an alkyne donor for immobilization of the CS onto 3-azidopropyl-functionalized silica gel (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…The higher reactivity and selectivity of phenyl chloroformate towards C6-OH versus C2-OH and C3-OH have already been reported (Elschner et al 2014;Ganske and Heinze 2018). In a previous study, we have optimized the protocol towards quantitative oxycarbonylation of C6-OH (Bui et al 2022b) and also reported on the optimization and successful aminolysis reaction between the polysaccharidic carbonates (Bui et al 2022a). The obtained phenyl carbonate served as a reactive intermediate for subsequent aminolysis with propargylamine yielding a propynyl carbamate moiety as an alkyne donor for immobilization of the CS onto 3-azidopropyl-functionalized silica gel (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…In this study, the effects of drilling additives, namely, polyanionic cellulose (PAC), carboxymethyl cellulose (CMC) polymers, and starch, on foaming stability were examined. These additives were specifically chosen for their environmentally friendly characteristics as they are derived from renewable and natural sources. …”
Section: Resultsmentioning
confidence: 99%
“…Cellulose derivative 5 was synthesized by oxycarbonylation of C6-OH of cellulose derivative 4 with phenyl chloroformate to prepare a precursor, which subsequently was to be converted into cellulose derivatives 6R and 6S by carbonate aminolysis. Phenyl chloroformate was chosen as a reagent due to its higher reactivity compared to p-nitrophenyl chloroformate (Bui et al 2022c;Bui et al 2022a). FTIR and solid-state 13 C NMR spectra of cellulose derivatives 5 versus 4 are shown in Fig.…”
Section: Cellulose 23-bis(35-dimethyl Phenyl Carbamate)-6-(phenyl Car...mentioning
confidence: 99%
“…Carbonate aminolysis was shown to be an efficient path towards the introduction of carbamate functionalities onto cellulose (Elschner et al 2013;Ganske and Heinze 2018;Bui et al 2022c), besides the routinely used isocyanate chemistry (Hearon et al 1943a;Hearon et al 1943c;Heard and Suedee 1996;Khan et al 2008;Labafzadeh et al 2014). However, the former way offers higher flexibility due to the greater availability of amines compared to the rather limited choice of available isocyanates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation